Boska władza reżysera. Karel Hugo Hilar – pierwszy nowoczesny reżyser w czeskim teatrze - Czachór, Sylwia (Wydawnictwo Naukowe UAM, 2013)
The aim of this research was to characterize changes in the perception of a function of theatre director at the begging of the 20th century. The Czech theatrical culture taking the pattern of great European theatre reformers of thattime, created a genuine theatrical theory of directing. Its first representative and implementer was Karel Hugo Hilar. His work was based on an assumption that a director is the highest instance in a preparation of performance, that can be compared only to a role of a sovereign. Moreover, Hilar was the first in the Czech cultural context to call a director the creator of a scenic reality. A reality that would represent a current world view transformed by theatrical means and the creative imagination of an artist.
The Divinity of Director’s Power. Karel Hugo Hilar – the First Modern Czech Theatre Director
Keywords: 20th century Czech theatre; Hilar; Reinhardt; Craig; theatre directing theory; scenic reality